Effects of Feedback-Based Visual Line-Orientation Discrimination Training for Visuospatial Disorders After Stroke. (February 2013) - Funk, Johanna; Finke, Kathrin; Reinhart, Stefan; Kardinal, Mareike; Utz, Kathrin S.; Rosenthal, Alisha; Kuhn, Caroline; Müller, Hermann; Kerkhoff, Georg
Background . Patients with right or more rarely left parietotemporal lesions after stroke may have profound visuospatial disorders that impair activities of daily living (ADL) and long-term outcome. Clinical studies indicate improvements with systematic training of perception. Studies of perceptual learning in healthy persons suggest rapid improvements in perceptual learning of spatial line orientation with partial transfer to nontrained line orientations. Objective . The authors investigated a novel feedback-based perceptual training procedure for the rehabilitation of patients after stroke. Methods . In an uncontrolled trial, 13 participants showing profound deficits in line orientation and related visuospatial tasks within 12 to 28 weeks of onset performed repetitive feedback-based, computerized training of visual line orientation over4 weeks of treatment. Visual line-orientation discrimination and visuospatial and visuoconstructive tasks were assessed before and after training. Results . The authors found ( a ) rapid improvements in trained but also in nontrained spatial orientation tests in all 13 participants, partially up to a normal level; ( b ) stability of the obtained improvements at 2-month follow-up; ( c ) interocular transfer of training effects to the nontrained eye in 2 participants suggesting a central, postchiasmatic locus for this perceptual improvement; and ( d ) graded transfer of improvements to related spatial tasks, such as horizontal writing, analog clock reading, and visuoconstructive capacities but no transfer to unrelated measures of visual performance. Conclusions . These results suggest the potential for treatment-induced improvements in visuospatial deficits by feedback-based, perceptual orientation training as a component of rehabilitation after stroke.